Optimal Overall Dimensions of a Surface Acoustic Waves Ring Resonator - S. Yu. Shevchenko; D. A. Mikhailenko (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. In previous works, the authors considered the frequency characteristics of sensitive elements made of various materials in the form of a ring resonator on surface acoustic waves (SAW), along with their fixing methods in the housing, the influence of external factors, and an optimal topology of the interdigital transducer of the ring resonator. Further, the need arose to study the dependence of the sensitivity of the sensitive element and the maximum acceleration load on its dimensions, as well as to analyze the characteristics of the manufactured experimental samples in comparison with the simulated values.Aim. To determine optimal dimensions of the sensitive element of a ring resonator and to confirm the adequacy of the constructed models by comparing the characteristics of experimental samples with those obtained by computer simulation.Materials and methods. The theoretical part of the research was carried out using the finite element method. Mathematical processing was implemented in AutoCAD and COMSOL Multiphysics.Results. Three overall dimensions of the sensitive element of a ring resonator were proposed: 1500, 3000 and 4500 µm. The characteristics of sensitive elements made of lithium niobate with the above dimensions were studied. Thus, the resonance frequency for 1500, 3000 and 4500 µm samples comprised 207.99, 104.10 and 68.99 MHz, respectively. The maximum acceleration experienced by a cantilever with a radius of 1500, 3000 and 4500 µm was found to be 191 132, 84 958 and 37 514g, respectively. Dependence graphs of the maximum acceleration and sensitivity on the ratio of the radius of the console to its height are presented. The adequacy of the constructed model was confirmed, i. e., the resonance frequency for 1500, 3000 and 4500 µm experimental samples comprised 218.17 MHz (4.67 % discrepancy with computer simulation), 109.23 MHz (4.69 %) and 72.88 MHz (5.34 %), respectively.Conclusion. The sensitivity and maximum acceleration load of the sensitive element of a SAW ring resonator directly depends on the ratio of the cantilever radius to its height, with higher sensitivity values correlating to lower values of maximum acceleration load. For each material, these dependencies are unique. The interdigital transducer bus size has little effect on the frequency response. The previously presented simulations were confirmed by experimental samples with a difference in resonance frequencies of less than 5.5 %.